Interpersonal Synchronization, Motor Coordination, and Control Are Impaired During a Dynamic Imitation Task in Children With Autism Spectrum Disorder - Xavier, Jean; Gauthier, Soizic; Cohen, David; Zahoui, Mohamed; Chetouani, Mohamed; Villa, François; Berthoz, Alain; Anzalone, Salvatore (Frontiers in Psychology, 2018)
Background: Impairments in imitation abilities have been commonly described in children with autism spectrum disorder (ASD). How motricity in interpersonal coordination impacts imitation, during long lasting semi-ecological conditions, has not been carefully investigated. Methods: 85 children and adolescents (39 controls with typical development, TD; 29 patients with ASD; 17 patients with developmental coordination disorder, DCD), aged 6 to 20 years, participated to a behavioral paradigm in which participants, standing and moving, interacted with a virtual tightrope walker standing and moving as well. During the protocol, we measured automatically and continuously bodily postures and movements from RGB sensor recording to assess participants’ behavioral imitation. Results: We show that (1) interpersonal synchronization (as evidenced by the synchrony between the participant’s and the tightrope walker’s bars) and (2) motor coordination (as evidenced by the synchrony between the participant’s bar and its own head axis) increased with age and were more impaired in patients with ASD. Also, motor control as evidenced by the movement angle standard deviations of participants’ bar and head were significantly impaired in ASD compared to TD or DCD. Conclusion: Interpersonal synchronization and motor coordination during ecological interaction show both subtle impairment in children with ASD as compared to children with TD or DCD. These results questioned how motricity mature in terms of motor control and proprioception in children with ASD.